Classics and Celtic literary modernism : Yeats, Joyce, MacDiarmid and Jones - Baker, Gregory, 1980- (Cambridge : Cambridge University Press, 2022)
Celtic modernism had a complex history with classical reception. In this book, Gregory Baker examines the work of W. B. Yeats, James Joyce, David Jones and Hugh MacDiarmid to show how new forms of modernist literary expression emerged as the evolution of classical education, the insurgent power of cultural nationalisms and the desire for transformative modes of artistic invention converged across Ireland, Scotland and Wales. Writers on the 'Celtic fringe' sometimes confronted, and sometimes consciously advanced, crudely ideological manipulations of the inherited past. But even as they did so, their eccentric ways of using the classics and its residual cultural authority animated new decentered idioms of English - literary vernaculars so fragmented and inflected by polyglot intrusion that they expanded the range of Anglophone literature and left in their wake compelling stories for a new age.
Introduction: " ... at once the bow and the mark": Classics and Celtic Revival -- "A noble vernacular"? Yeats, Hellenism and the Anglo-Irish Nation -- "Hellenise it." Joyce and the Mistranslation of Revival -- "Straight Talk, Straight as the Greek!" Ireland's Oedipus and the Modernism of Yeats -- "Heirs of Romanity": Welsh Nationalism and the Modernism of David Jones -- "A form of Doric which is no dialect in particular:" Scotland and the Planetary Classics of Hugh MacDiarmid.
Title from publisher's bibliographic system (viewed on 24 Jan 2022).
Keywords: Yeats, W. B. -- 1865-1939 -- Criticism and interpretation; Jones, David, -- 1895-1974 -- Criticism and interpretation; MacDiarmid, Hugh, -- 1892-1978 -- Criticism and interpretation; Joyce, James, -- 1882-1941 -- Criticism and interpretation; English literature -- Classical influences